Experience of using the state of emergency in Ukraine (Journal of actual problems of jurisprudence, 2019)
The article presents the analysis of scienti fic papers and regulations regarding the order of administration that the state of emergencyin Ukraine. In addition, attention to the practice of the regime on the territory of Ukraine, namely content analysis procedures forimposing a state of emergency in the Autonomous Republic of Crimea. Also identi fi ed ways to improve current legislation of Ukraineon the use of state of emergency, namely proposed amendments and clari fi cation to the Law of Ukraine «On Legal Status of emergency»to clarify the purpose of the introduction of a state of emergency, and the order of administration, etc.